A toolkit to prioritise interventions in climate-smart agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
This Climate Smart Agriculture Prioritisation toolkit includes bottom-up, bio-economic and data-driven approaches to support sub-national and local scenario building and facilitate policy making. The toolkit can guide investment decisions and highlight the implications of such investments on income, employment, food security, and the environment.